Analisis Kriteria perbankan dalam Sistem Bank Umum Kelompok Usaha (Buku) di Indonesia - Agus Sumantri, Bambang (EKSYAR: Jurnal Ekonomi Syariah & Bisnis Islam, 2015)
Writing in this journal is to create a map and analyze the shape of banking in Indonesia both conventional banks and Islamic banks. Wherein analyzing touch it with the type and criteria in a system Banking Commercial Bank Business Group (BOOK) that regulate core capital and scope in respect of the products and activities.